Morphology and Photoluminescence Properties of Lu2O3:Eu Films Prepared by LCVD Method. (12th February 2020) - Chang, Jingyu; Qi, Yunhang; Yang, Yunling; Yuan, Rui; Xu, Zhan; Li, Qianli; Dai, Lingen; Lu, Baoqi; Feng, He; Zhao, Jingtai
Abstract : Efficient and dense scintillator Lu2 O3 :Eu is one of the most promising candidates used for high resolution hard X-ray imaging detector. In this paper, Lu2 O3 :Eu films were prepared through laser chemical vapor deposition on single crystal yttrium stabilized zirconia substrates. The structure and morphology of the films were investigated by X-ray diffraction and scanning electron microscopy. Lu2 O3 :Eu films, with micro-columnar and single crystal morphologies, were obtained through adjusting growth parameters. The growth mechanisms were also discussed based on related phenomena. The photoluminescence properties of the films were measured and discussed, including photoluminescence excitation, photoluminescence spectra and photoluminescence decay curves.